Islam and Iran’s post-revolution war on drugs: a Durkheimian analysis - Zahra Farhadi Alashti; Abdolreza Javan Jafari Bojnordi (IAIN Salatiga, 2021)
Despite widespread criticism of the failure to achieve the predetermined penal and criminological goals of Iran’s post-revolution war on drugs, the harsh penal practices remain in practice until today. By applying Durkheim’s attitude in his last major work, the elementary forms of religious life, the purpose of this paper is to analyze the rationale for the Iranian war on drugs from the perspective of religion and not penal code or criminology. This article draws on qualitative analysis, and data were collected through analysis of legal documents, literature discussing the war on drugs, news reports, and past journals. The findings of this article reveal that the war on drugs originates from an understanding that attributes evilness to such criminals to prevent the disintegration of Islamic society. This approach blurs the line between “preserving Islam” and the “Islamic society,” and the repressive policies are consecrated to avoid social disintegration. Our study confirms Durkheim’s attitude in which sacredness is highly contagious. Following the sanctity of preserving Islamic society from the profanity of drug crimes, the application of specialized mechanisms for fighting drugs, such as anticipating specialized criminal courts for violation of sacred values, setting special legislative authorities for the crime, and meting out harsh punishments, have all become plausible. Accordingly, all these practices would be treated as sacred because they are associated with fighting the “profane” phenomenon of drugs.